2010
DOI: 10.1590/s0101-31222010000200007
|View full text |Cite
|
Sign up to set email alerts
|

Adubação nitrogenada, potássica e fosfatada na produção e germinação de sementes de capim quicuio-da-Amazônia

Abstract: RESUMO -Devido à falta de informações relacionadas à adubação de plantas forrageiras para a produção de sementes, nota-se a necessidade de se estudar a influência de doses de nutrientes que proporcionem aumento de produtividade e obtenção de sementes de melhor qualidade. Foram realizados dois experimentos com o objetivo de verificar o efeito de doses de nitrogênio e fósforo e de doses de nitrogênio e potássio sobre a produção e qualidade de sementes de Brachiaria humidicola (Rendle) Schweick. Em ambos, o delin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 11 publications
1
5
0
2
Order By: Relevance
“…This occurs because, during the germination process, proteins are hydrolyzed to supply N and C to the embryonic axis, which promotes adequate initial development of the seedlings (Buckeridge et al, 2004). Similar responses regarding the effect of N on seed germination were also observed by Deminicis et al (2010), who reported that N application (200 kg N ha −1 ) during the initial stage of development (on the day of the staging of the herbage) positively influenced the germination of creeping signalgrass seeds.…”
Section: Physiological Seed Qualitysupporting
confidence: 80%
See 3 more Smart Citations
“…This occurs because, during the germination process, proteins are hydrolyzed to supply N and C to the embryonic axis, which promotes adequate initial development of the seedlings (Buckeridge et al, 2004). Similar responses regarding the effect of N on seed germination were also observed by Deminicis et al (2010), who reported that N application (200 kg N ha −1 ) during the initial stage of development (on the day of the staging of the herbage) positively influenced the germination of creeping signalgrass seeds.…”
Section: Physiological Seed Qualitysupporting
confidence: 80%
“…topdressed during the vegetative phase plus 100 kg N ha −1 topdressed at panicle initiation). The N rate (150 kg N ha −1 ) applied to Llanero creeping signalgrass was determined by scientific research (Deminicis et al, 2010;Catuchi et al, 2013). These authors found that doses between 127 and 200 kg N ha −1 provided the highest yields of pure seeds of creeping signalgrass.…”
Section: Experimental Sitementioning
confidence: 99%
See 2 more Smart Citations
“…The country has increased its planted pasture area in approximately 341% from 1970 to 2006. Currently, it is mentioned as the largest supplier of seeds for cultivation and regeneration of pasture of the domestic market and largest exporter of tropical forage plants worldwide (Deminicis et al, 2010).…”
Section: Introductionmentioning
confidence: 99%